Child’s temperament and maternal coping with child’s negative emotions related to four-year-old children’s delay of gratification - Breidokienė, Rima; Jusienė, Roma (Psichologija, 2014)
Numerous researchers agree that the early development of a delay of gratification abilities is crucial for a successful adjustment in childhood, adolescence, and adulthood, thus it is very important to understand its precursors and antecedents. Although strong evidence indicates the temperamental nature of the ability to delay gratification, socialization factors also shape the way innate characteristics are expressed and developed. However, there have been relatively few studies examining how early parental and child’s innate variables jointly predict the development of delay of gratification in early childhood in a low-risk healthy children’s sample. Thus, the main purpose of this study was to analyze the child’s temperament traits, maternal distress, and coping with the child’s negative emotional responses related to delay of gratification of 4-years-old children. The participants of this study are 142 children (71 boys and 71 girls), participating in the ongoing longitudinal study on the early development of self-regulation. Children’s delay abilities were evaluated using two laboratory tasks at the age of 4 years: “Delay of Snack” and “Wrapped Gift” (adopted from Kochanska et al., 1996). The empirical data about biological and psychosocial factors was provided by mothers on the 2nd-3rd day after delivery, 3 and 18 months, 2 and 3 years after the child’s birth. Maternal responses to children’s negative emotions at children’s age of 3 years were assessed using the Coping with Children’s Negative Emotion Scale (CCNES, Fabes, Eisenberg & Bernzweig, 1990) and child’s temperament (effortful control, negative affectivity, and extraversion) at children’s age of 3 years was assessed using the Children’s Behavior Questionnaire Short Form (Rothbart et al., 1994; Rothbart et al., 2001). Children whose mothers reported less negative experiences during the second and third years of the child’s life demonstrated higher abilities of a delay of gratification. This may show the importance of maternal emotional wellbeing for the development of children’s self-regulation. Optimal delay abilities, measured by “Wrapped Gift”, were predicted by the non-presence of maternal stressful events. Optimal delay abilities, measured by a “Delay of Snack”, were predicted by a lower maternal distress 2 years postpartum and higher non-supportive maternal responses to children’s negative emotions. However, the latter non-supportive maternal responses were related to higher abilities of a delay of gratification only for children with a higher negative affectivity and a higher extraversion. This may show that maternal non-supportive responses may be beneficial for children with certain temperamental traits.